Alzheimer's Disease Challenges for the Future - Zerr, Inga (IntechOpen, 2015)
There is a wide scope of clinical phenomenology in Alzheimers disease, regarding the age of onset, presenting features, rate of progression and appearance of other clinical manifestation. Although clinical appearance and neuropathological hallmarks have been defining AD since its first description, major factors which trigger pathology are still unknown. The role of comorbidity is discussed controversially. Important environmental risk factors in AD development are continuous stress, low education and cardiovascular risk factors such as alcohol intake, smoking, hypertension. The role of lipids and cholesterol has been recognized, but the relevant pathogenetic steps are still to be identified. There is an urgent need to understand molecular disease pathogenesis in order to develop early therapeutic targets for the disease.